The Effect of Profitability, Leverage, and Company Size on Dividend Policy: A Case Study of Transportation Companies Listed on the Indonesia Stock Exchange for the 2017-2022 Period - Sartika, Dewi; Rilla Gantino (HM Publisher, 2023)
The company's decision in determining the amount of dividends to be distributed to shareholders can be influenced by various factors, including profitability, leverage, and company size. This study aimed to analyze the effect of profitability, leverage, and company size on dividend policy in transportation companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. In this study, Profitability is proxied by return on equity (ROE), Leverage is proxied by the debt to equity ratio (DER), and company size is proxied by the logarithm of total sales (Ln total sales). While the dividend policy is proxied using the dividend payout ratio (DPR) with the retention ratio formula by dividing retained earnings and net income balance, then 1 minus the RR value. The sampling technique in this study used a purposive sampling technique. There are 22 transportation companies listed on the Indonesia Stock Exchange for the period 2017 – 2022 which are used as samples in this study. The type of data used is quantitative data from secondary data sourced from financial reports. The data analysis method used is multiple linear regression analysis. The results of the study show that profitability, leverage, and company size simultaneously influence dividend policy. Partially profitability has a positive effect on dividend policy. Meanwhile, leverage has no negative effect on dividend policy, and company size has no positive effect on dividend policy.